Evolutionary dynamics of nematode operons: Easy come, slow go - Qian, Wenfeng; Zhang, Jianzhi (Genome Research, 2008)
Operons are widespread in prokaryotes, but are uncommon in eukaryotes, except nematode worms, where ∼15% of genes reside in over 1100 operons in the model organism Caenorhabditis elegans. It is unclear how operons have become abundant in nematode genomes. The “one-way street” hypothesis asserts that once formed by chance, operons are very difficult to break, because the breakage would leave downstream genes in an operon without a promoter, and hence, unexpressed. To test this hypothesis, we analyzed the presence and absence of C. elegans operons in Caenorhabditis briggsae, Caenorhabditis remanei, and Caenorhabditis brenneri, using Pristionchus pacificus and Brugia malayi as outgroups, and identified numerous operon gains and losses. Coupled with experimental examination of trans-splicing patterns, our comparative genomic analysis revealed diverse molecular mechanisms of operon losses, including inversion, insertion, and relocation, but the presence of internal promoters was not found to facilitate operon losses. In several cases, the data allowed inference of mechanisms by which downstream genes are expressed after operon breakage. We found that the rate of operon gain is ∼3.3 times that of operon loss. Thus, the evolutionary dynamics of nematode operons is better described as “easy come, slow go,” rather than a “one-way street.” Based on a mathematic model of operon gains and losses and additional assumptions, we projected that the number of operons in C. elegans will continue to rise by 6%–18% in future evolution before reaching equilibrium between operon gains and losses.